Efffect of government intervention on stock returns. - Ong, Boon Kang. (2008)
This study looks into the effect of the Malaysian government's intervention in its local stock market via stock purchases through five key government linked investment funds. The results of this study indicate that the intervention generally produces no significant effect on stock returns around all three dates of interest.